Proposal of a prototype of foundry system to reuse waste of low melting point alloys by means of conductive heat transfer - Navarro Ita, Aaron Jorge Jose (2025)
Nowadays, the management of foundry machinery is expensive and complicated, not only because of the energy used, but also because of the polluting, lengthy and dangerous process. This perspective is relevant given that, in many metallurgical micro-enterprises, and even educational center laboratories, waste is generated that is sold at a very low price and a product made from virgin material is purchased, increasing the expense, time and natural consumption in the foundry process. The following innovation work develops a prototype proposal for a foundry process that provides optimization for the metallurgical industry on a smaller scale. The approach includes placing the material (waste) in a heating system that works through a conduction transfer, which is theoretically supported due to the short-circuit process complemented by Joule's Law, which is the conversion of electrical energy into heat until obtaining the molten material. Finally, an analysis of the results is carried out that demonstrate the effective mechanism after the use of a low melting point material as an example (Metal of Wood) after melting at a certain time (30 seconds) and temperature (88.3 ° C) with the efficient use of the converted amperage (192 A) and voltage (1.517 V) and the only resource of a conventional plug at 220V and 10A. In this sense, a low cost of obtaining is generated after decreasing the voltage and increasing the current, obtaining a reduction in the use of energy of -41.75% compared to other foundry processes such as induction.